2017
DOI: 10.1080/09712119.2017.1355806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary inclusion of dried citrus pulp on growth performance, carcass characteristics, blood metabolites and hepatic antioxidant status of rabbits

Abstract: View related articles View Crossmark data Citing articles: 2 View citing articles Effect of dietary inclusion of dried citrus pulp on growth performance, carcass characteristics, blood metabolites and hepatic antioxidant status of rabbits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
(42 reference statements)
6
9
0
Order By: Relevance
“…The highest (P≤0.05) value of TAO recorded with 9% LPT group when compared to all test groups. This result confirmed by Lu et al (2017) who found that hepatic total anti-oxidant enzyme was significantly higher in experimental groups than control group for growing rabbits fed citrus pulp up to 21%in the diet. Immunoglobulin G (IgG) significantly (P≤0.05) increased with rabbit fed 9%LPT compared to control and other experimental groups.…”
Section: Biochemical Analysissupporting
confidence: 83%
“…The highest (P≤0.05) value of TAO recorded with 9% LPT group when compared to all test groups. This result confirmed by Lu et al (2017) who found that hepatic total anti-oxidant enzyme was significantly higher in experimental groups than control group for growing rabbits fed citrus pulp up to 21%in the diet. Immunoglobulin G (IgG) significantly (P≤0.05) increased with rabbit fed 9%LPT compared to control and other experimental groups.…”
Section: Biochemical Analysissupporting
confidence: 83%
“…Suliman and Ameen (2018) who found that total lipids, cholesterol, triglycerides, AST, ALT and urea had significant (p<0.05) difference among all rabbit groups fed lemon pulp treated by yeast when compared to control group. However, Jingzhi et al (2018) found that AST did not significantly change in rabbits at 21% citrus pulp. Generally, the experimental diets were significantly different (p<0.05) in some blood parameters among rabbit fed dietary containing 5% and 10% OP treated by S. cerevisiae yeast.…”
Section: Plasma Parametersmentioning
confidence: 87%
“…The improvement of FI by yeast treatment confirmed by Shehu et al (2014) who found intake of growing rabbits increased (p<0.05) in rabbits fed diets supplemented 60g/kg S. cerevisiae yeast. On the contrary, FI, BWG and FCR of growing rabbits didn't affect by the dietary citrus pulp (Lu et al, 2018) and yeast supplementation (Belhassen et al, 2016). The DM intake of growing rabbits recorded did not significantly affected by yeast supplementation (Khanna et al, 2014).…”
Section: Growth Performancementioning
confidence: 99%
“…The alteration of immune organ relative weight would influence animals' immune function. Lu et al (2018) reported that the thymus indexes of the citrus pulp inclusion groups demonstrated an increased trend compared with those of the control group, which indicated that the dietary inclusion of citrus pulp benefitted the health of rabbits. In mice, lack of vitamin B6 inhibits lymphocyte proliferation and maturation and reduces thymus weight (Ha et al 1984).…”
Section: Effect Of Dietary Supplement Of Vitamin B6 On Immune Organs mentioning
confidence: 94%
“…Nutritional status is the most important factor influencing immune defense mechanisms of animals, deficient or excess levels of nutrients can alter the immune system. Lu et al (2018) reported that inclusion of increased citrus pulp could improve immunization and hepatic antioxidant status of growing rabbits. Pourhossein et al (2015) found that Citrus sinensis peel extract significantly improves the serum levels of IgM, and IgG in broiler chickens.…”
Section: Effect Of Dietary Supplement Of Vitamin B6 On Serum Immune Mmentioning
confidence: 99%